Guiagens em Brasília Educação patrimonial na cidade modernista ou como flanar pelo plano piloto - Raquel Mello de Souza (2019)
This essay narrates the construction process of a patrimonial education guide to the city of Brasília, committed on recovering Lúcio Costa´s memory as the urbanist and architect responsible for the conception of the modernist urbanism of the federal capital of Brazil, which granted it recognition as Cultural Patrimony of Humanity, by UNESCO in 1987. It also aims to contribute in revealing the patrimonial signification of the federal capital, inviting the visitor to acquaint on the public space of the city in order to observe places of memory that are relevant to the inhabitant, who changes, shapes and adapts the modernist urban planning, in order to think over the contradictions evoked by living in a patrimonialised space. Starting with the subjective narrative of the author, a former resident of the city, and by the bibliographic review of academic, poetic and photographic narratives about the city, this essay is rooted on observations about the city, the experience, the narrative and the patrimonial education. Thus, the theoretical-methodological choices are based on the academic production upon the cities of scholars affiliated with Walter Benjamin, Georg Simmel, Michel de Certeau, Marc Augé, Jane Jacobs, James Holston and Jan Gehl. As well as in the studies on Patrimony and Heritage Education of Néstor Garcia Canclini, Françoise Choay, José Reginaldo Santos Gonçalves, Ulpiano Toledo Bezerra de Meneses, José Newton Coelho Meneses and Leandro Henrique Magalhães. The technical product resulted from this essay, composed of a booklet with a tied-in map, is denominated Guiagens em Brasília - roteiros temáticos para a educação patrimonial